Ex vivo application of endocytoscopy for determining the longitudinal extent of bile duct cancer: a pathological analysis of 28 resected cases. (18th September 2014) - Yoshikawa, Toru; Hakamada, Kenichi; Ogasawara, Hiroshi; Kimura, Norihisa; Kudo, Daisuke; Sakamoto, Yoshiyuki; Ishido, Keinosuke; Toyoki, Yoshikazu; Morohashi, Satoko; Kijima, Hiroshi
Abstract Background The aim was to examine the diagnostic ability of an endocytoscope system (ECS) for detecting the longitudinal extent of bile duct cancer. Methods We observed the surfaces of the bile duct of 28 consecutive patients undergoing biliary surgery both directly and under methylene blue staining by using an ECS. Based on the change in the microvascular caliber, abnormal vascularity, structural atypia, and cellular atypia, we created an ECS score. Results The ECS score produced a median value of 1 (range 0–3) point in normal bile ducts, 3 (0–6) points in cholangitis, 9 (1–10) points in carcinoma in situ (CIS), and 8 (3–11) points in invasive cancer. A significant difference in the scores between cancerous and non‐cancerous lesions was found (P < 0.001). The ECS score was able to distinguish non‐cancerous lesions from cancerous lesions using the cut‐off value of a score less than 5, the accuracy being 92.1%, with a sensitivity of 91.1% and specificity of 93.5%. Conclusions With ECS observation of bile duct specimens, the newly created ECS score was able to clearly distinguish non‐cancerous lesions from cancerous lesions. This ECS score method should be validated in the differentiation of various BilIN lesions in the future.